Construction and preliminary analysis of landslide database triggered by heavy storm in the parallel range-valley area of western Chongqing, China, on 8 June 2017 - Liu, Jielin; Xu, Chong (Frontiers in Earth Science, 2024)
On June 8, 2017, a heavy storm struck the parallel ridge-valley area of western Chongqing, resulting in serious urban waterlogging and landslides, which led to severe impacts on infrastructure and damage to private property. Based on highresolution optical satellite images, this paper comprehensively identified the landslides triggered by this rainfall event, and established a corresponding landslide database. The database takes the landslide area density and landslide number density as the main indicators, and combines the lithology characteristics to analyze the spatial distribution of landslides. The results show that this event triggered 487 landslides in an area of 583 km 2 , involving an area of about 485,587 m 2 , accounting for about 0.083 % of the study area. The average landslide number density is 0.84 num/km 2 , the highest value of landslide number density can reach 55.6 num/km 2 , and the maximum landslide area density is about 6.4 %. These landslides are mainly distributed in the southern foothills of the Huaying Mountain, especially in the weak interlayer lithology area. The database provides scientific reference and data support for exploring the mechanism of landslides in western Chongqing and reducing the risk of landslide disasters under the background of rapid development of local society.